SOSIALISASI PENCEGAHAN DBD DAN PEMBERANTASAN SARANG NYAMUK DI DESA PONGKAR, KARIMUN - Arianti, Nisha Desfi; Angelina; Indah Wahdini; Maulana Riza Sandika Sutra; Nensi Setianingrum; Siti Aisah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Dengue hemorrhagic fever, also known as dengue fever, is transmitted by female Aedes aegypti mosquitoes with the main target being the human circulatory system, characterized by quite serious fever symptoms. Dengue fever must be treated seriously and become a regional priority program considering the number of cases tends to increase yearly, one of which is Karimun Regency. As of August 2022, dengue fever cases in Karimun reached 628, the highest number of cases in the last four years. So this has become one of the focuses of attention of Community Service Students, Karimun University. The stages in the implementation of this activity are divided into four stages: Submitting a Program; Program Exposure; Data Collection on DHF Cases; Socialization. This socialization activity was carried out on July 17, 2022, in Pongkar Village, Karimun, by Team 1 with Lavender and Anyelir Integrated Services Post. What was conveyed in the socialization was a general introduction to Dengue Hemorrhagic Fever (DHF), the causes of DHF and how to prevent it. This program requires community participation to maintain the environment of their homes and surrounding settlements. From the implementation of this community service, an output is produced, namely the dissemination of general knowledge about Dengue Hemorrhagic Fever (DHF) Prevention and Mosquito Nest Eradication in Pongkar Village so that it can help minimize dengue cases in Pongkar Village in particular and Karimun Regency in general.